Cross-border or online: Tax competition with mobile consumers under destination and origin principle - Laura Birg (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
This paper studies the effect of an online retailer on spatial tax competition with mobile consumers. Under non-cooperative Leviathan governments, tax treatment of online purchases according to the destination principle mitigates tax competition; tax treatment of online purchases of online purchases according to the origin principle enhances tax competition. Cooperation between government eliminates the potential pro-competitive effect of the online retailer: Under both tax treatments, the online retailer weakens tax competition. For a sufficiently low tax rate in the country hosting the online retailer, welfare in the online retailer's home country is higher under the origin principle, while welfare in the other country is higher under the destination principle. For a sufficiently low tax differential between both countries, global welfare is higher under the destination principle.
Keywords: F12; H20; L13; 330; tax competition; cross-border shopping; online retailer; destination principle; origin principle